The readership indicators in Poland and programs promoting the reading - Wojciechowska, Maja (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
The results of the recently published report by the National Library of Poland contain alarming data. Polish society is slowly losing tangency with literature, and therefore the competencies of interpretation, analysis and synthesis of the texts, including literary texts and others. For this purpose, librarians, individuals and institutions interested in the promotion of reading more and more often organise numerous events addressed to various audiences: children, youth, seniors, young parents, but also socially excluded people. The following article presents selected Polish initiatives designed to address the promotion of reading.